PENGARUH TANAMAN KEDELAI SEBAGAI TANAMAN SELA (Glycine max L. Merril) TERHADAP CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS), ABU BOILER DAN LIMBAH CAIR PABRIK KELAPA SAWIT (LCPKS) PADA GAWANGAN KELAPA SAWIT YANG BELUM MENGHASILKAN DI LAHAN GA - Onky Febrion; Nelvia '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aimed to study the application of the combination of compost of palm oil empty fruit bunches (POEFB), boiler ash and liquid waste of palm oil industry to growth and yield of soybean (Glycine max L. Merril) on palm oil plantations in peat land. The research was conducted at the Kualu Nenas Village, Kampar Regency,  Riau Province from January to April 2013. The research used Randomized Block Design consists of nine treatment (A : without treatment/control, B : 1.45 kg compost of POEFB per plot, C : 1.45 kg compost   + 145 g boiler ash per plot, D : 1.45 kg compost + 290 g boiler ash per plot, E : 1.45 kg compost + 435 boiler ash per plot, F : 1.45 kg compost + 8,64 ml liquid waste per plot, G : 1.45 kg compost + 145 g boiler ash + 8.64 ml liquid waste per plot, H : 1.45 kg compost + 290 g boiler ash + 8.64 ml liquid waste per plot and I : 1.45 kg compost + 435 g boiler ash + 8,64 ml liquid waste per plot) each treatment repeated three times. Parameters observed were plant height, number of primary branches, age flowering, number of pods, percentage of pithy pods and weight of dry seed per plot. The research shows that application of 1.45 kg empty fruit compost of POEFB + 145 to 435 g boiler ash + 8.64 ml liquid waste per plot can increase plant height, number of pods and weight of dry seed per plot significantly compared with control, but not significantly compared with the another treatments. Key words : compost, boiler ash, liquid waste, peat land, soybean